Consumer-based new product development for the food industry - Porretta, Sebastiano; Moskowitz, Howard; Gere, Attila (Royal Society of Chemistrty, 2021)
This is the first book that describes and explains food development from the point of view of the consumer rather than from the top down approach.
Keywords: Food industry and trade.; New products.; Consumer behavior.; elektronické knihy; electronic books